The Precious Knowledge of Oral Cultures: Converging Analyses of Italian Peasantry and the Haudenosaunee First Nations People. A Case Study - Della Rossa, David (Italian Canadiana)

(untitled) (Iter Press, 2022)
This case study documents the ancestral oral knowledge of Italian peasant culture and the Haudenosaunee people in informing an ecologically sustainable land ethic. In preserving the knowledge of their oral traditions and comparing the two oral cultures, humanity gains a deeper understanding into the insight and wisdom of oral stories. These two oral cultures point towards a sustainable and interdependent way of knowing and living on the land that will ensure a healthy and nurturing Earth for future generations.